IDENTIFIKASI KEBUTUHAN PENGGUNAAN MEDIA PEMBELAJARAN IPAS BERBASIS WEB INTERAKTIF DI JENJANG SEKOLAH DASAR PADA ERA DIGITAL - Ari Yuniawan; Purwo Susongko; Suriswo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The lack of use of innovative digital learning media in the teaching and learning process of Natural and Social Sciences (IPAS) in elementary schools is still a major problem in the era of educational transformation. Teachers still predominantly use conventional media such as textbooks and worksheets, while students show high interest in visual, interactive and multimodal learning. This research aims to analyze the need for developing interactive digital-based science learning media that can support contextual and interesting learning. The approach used is descriptive quantitative and descriptive qualitative, with the proportional cluster random sampling method. The research subjects consisted of school principals, teachers, students and parents in several elementary schools in Pemalang Regency. Data collection was carried out through Likert scale questionnaires and semi-structured interviews. The research results show that all groups of respondents expressed a high need for the development of digital learning media. School principals support digital innovation, teachers need flexible and visual media, students want learning that is fun and not boring, and parents are willing to accompany their children to study at home using technology-based media. Google Sites-based learning media is considered relevant because it is able to present material in various formats that are interesting and easy to access. This research emphasizes the urgency of collaboration between teachers, schools and parents in supporting digital learning as part of improving the quality of basic education